PENGARUH BUDAYA ORGANISASI DAN KEMAMPUAN ORGANISASI TERHADAP KOMITMEN ORGANISASI DI MADRASAH ALIYAH NEGERI 3 BATANG HARI - Delia Masmudah; Dini Haryati; Muhammad Yusup; Sukatin Sukatin; Mahdayeni; Zilawati (JURNAL ILMIAH NUSANTARA, 2025)
This research aims to describe, test and analyze the influence of organizational culture and organizational capabilities on organizational commitment at Madrasah Aliyah Negeri 3 Batang Hari. This research uses quantitative research methods with a survey design that uses a questionnaire as a data collection tool. Data analysis used multiple regression analysis with the help of the Statistical Package for the Social Sciences (SPSS) program. Based on the research results obtained, it can be concluded that Organizational Culture has a significant effect on Organizational Commitment, namely tcount>ttable or 1.743>1.708. Organizational Capability has a significant effect on Organizational Commitment, namely tcount>ttable or 2.984>1.708. The results of the regression coefficient test show that organizational culture and organizational capabilities influence organizational commitment at Madrasah Aliyah Negeri 3 Batang Hari. The percentage contribution of the independent variable X1 (Organizational Culture) is 36.2% and X2 (Organizational Capability) is 62.0% on the dependent variable Y (Organizational Commitment) while the remaining 4.6% is influenced or explained by other variables. The conclusion of this research is that the level of Organizational Commitment at Madrasah Aliyah Negeri 3 Batang Hari is influenced by the variables Organizational Culture and Organizational Capability.